Rapid Implementation of a Multidisciplinary COVID‐19 Cytokine Storm Syndrome Task Force. Issue 3 (6th February 2021) - Ayesha, Bibi; Kumthekar, Anand; Jain, Ruchi; Patel, Sneha; Ramesh, Manish; Ferastraoaru, Denisa E; Hudes, Golda; Karagic, Merhunisa; Zafar, Sheema; Bartash, Rachel; Vasquez‐Canizares, Natalia; Kitsis, Elizabeth; et al.
Abstract : Objective: Patients with coronavirus disease 2019 (COVID‐19) can progress to a state of unregulated inflammation called cytokine storm syndrome (CSS). We describe formation and operation of a COVID‐19 multidisciplinary consultation service that was allowed to individualize treatment for critically ill patients with COVID‐19 during the pandemic. Methods: Institutional experts from different subspecialties formed a COVID‐19 CSS task force at Montefiore Medical Center, Bronx, NY. They agreed on a set of four clinical and six laboratory parameters that can help early identify COVID‐19 CSS. We describe the formation and implementation of the COVID‐19 task force. The case series description of the COVID‐19 CSS consultation cohort highlights consultation volume, baseline characteristics, clinical and laboratory parameters, and how biologic treatments were allocated to these patients. Results: Between April 4, 2020, and May 7, 2020, the COVID‐19 CSS task force was formed, consisting of adult and pediatric rheumatologists and allergy and immunology physicians. The task force evaluated a total of 288 patients, of whom 197 (68%) were male, the median (interquartile range [IQR]) age was 62 (51‐70) years, 122 (42%) were Hispanic, and 88 (31%) were Black or African American. The common presenting symptoms in all referred patients were dyspnea (85%) and diarrhea (80%). Thirty‐one patients who received biologic therapy were younger, with a median (IQR) age of 53 (32‐63) years, as opposed to 62.5 (52‐70) years in the nonbiologic group ( P = 0.008). A higher proportion receiving biologics was in the critical care setting (26 [84%] vs 151 [59%]; P = 0.006). Conclusion: To the best of our knowledge, this is the first multidisciplinary collaborative effort to provide individualized patient recommendations for evaluation and treatment of patients with COVID‐19 who may have CSS. This working model helped to devise an approach that may have identified patients who were most likely to benefit from biologic therapy in the absence of evidence‐based guidelines.